2022
DOI: 10.1088/1361-6463/ac7366
|View full text |Cite
|
Sign up to set email alerts
|

Low-thermal-budget n-type ohmic contacts for ultrathin Si/Ge superlattice materials

Abstract: Thermal budget is always a vital element in Si-based superlattice materials processing. In this work, a novel n-type ohmic contacting scheme with a low processing thermal budget is developed by combining the high-dose ion implantation and low-temperature alloying techniques. The optimized specific contact resistivity (ρc) is reduced to 6.18×10-3 Ω·cm² at a low thermal budget of 400 °C, and this is a result of the efficient low-temperature electrical activation in amorphous substances. It is indicated that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A schematic of a typical strained Si QW structure is depicted in figure 1(b), including a 2 nm-thick Si cap layer, a 30 nmthick relaxed SiGe barrier layer, and a strained Si QW with a thickness of ∼ 12 nm on top of a Si 0.75 Ge 0.25 virtual substrate. Then, enhancement-mode Hall bar-shaped field effect transistors (FETs) were patterned on the heterostructure following a standard fabrication process similarly described in a previous study [22], and the key steps of the integration flow are shown in figure 1(a). The source/drain contact regions were defined by heavy phosphorus ion implantation at a dose of 5 × 10 15 cm −2 , followed by a Ni/Al (10/200 nm) metal bilayer as the contact electrodes by e-beam evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…A schematic of a typical strained Si QW structure is depicted in figure 1(b), including a 2 nm-thick Si cap layer, a 30 nmthick relaxed SiGe barrier layer, and a strained Si QW with a thickness of ∼ 12 nm on top of a Si 0.75 Ge 0.25 virtual substrate. Then, enhancement-mode Hall bar-shaped field effect transistors (FETs) were patterned on the heterostructure following a standard fabrication process similarly described in a previous study [22], and the key steps of the integration flow are shown in figure 1(a). The source/drain contact regions were defined by heavy phosphorus ion implantation at a dose of 5 × 10 15 cm −2 , followed by a Ni/Al (10/200 nm) metal bilayer as the contact electrodes by e-beam evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Ohmic contacts providing a negligible resistance are desired for most silicon technologies. [10,11] However, achieving a near-perfect Ohmic contact with a nanoscale semiconductor is generally difficult. If brought in contact with moderately doped silicon most metals form a Schottky contact rather than an Ohmic contact.…”
Section: Introductionmentioning
confidence: 99%